Dimensions of powerlessness - Danziger, R; Danziger, Renée (1986)
﻿ This inquiry into the nature of political powerlessness begins with a definition which posits that Q is politically powerless to the extent that it is unable to promote and defend its interests within authoritative processes of value allocation. Political powerlessness is said to derive from Q's lack of relevant power resources; and from T's exploitation of this deficiency through its exercise of power over Q. Contrary to pluralist assumptions, it is argued that T may exercise political power over Q both within and beyond formal arenas of value allocation: the determining factor is not where political power is exercised, but rather that it prevents Q from satisfying its interests within these authoritative arenas. The above hypotheses are tested for their validity and utility by being applied to the experiences of the post-war agricultural work force in England. In particular, the study asks whether farmworkers' workplace powerlessness, as identified by Howard Newby in 'The Deferential Worker' (Penguin, Harmondsworth, 1979), has been compensated for by their Union's promotion and defence of agricultural workers' occupational interests at the formal, political level. Part One provides a theoretical, historical and descriptive setting for the empirical study. Part Two determines the extent to which the efforts of the Union and of its external political allies to influence the relevant value allocating institutions have resulted in the successful promotion and defence of farmworkers' objective interests. These interests are defined as: earning high wages (Chapter Four); living in housing which is independent from employment (Chapter Five); and ensuring a reasonable standard of occupational health and safety (Chapter Six). The study shows that the farmworkers' Union has been largely unable to compensate for its members' industrial weakness by taking political action. The Union's political powerlessness is attributed chiefly to its lack of relevant power resources; and to its resulting vulnerability to power exercises both within and beyond the formal political arena, all of which have weakened the Union within that arena. It is suggested finally that the Union's recent merger with the Transport and General Workers' Union provides farmworkers with access to new power resources which may allow for greater success in the future promotion of farmworkers' occupational interests.